2009
DOI: 10.1037/a0010738
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward adoption of evidence-based practices: A comparison of autism early intervention providers and children’s mental health providers.

Abstract: Across the country, states are reporting increases in the number of children with autistic spectrum disorders (ASD) served each year in the early intervention system. Research examining factors impacting the successful dissemination and implementation of evidence-based practice (EBPs) into service systems for these children is limited. Preliminary information indicates that adoption of EBPs is variable. Provider attitudes toward the adoption of EBPs may be one factor that limits or facilitates implementation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
104
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 60 publications
2
104
1
Order By: Relevance
“…Providers’ attitudes toward new clinical practices may hamper or facilitate the adoption of ESTs into practice settings. A quick measure of workers’ attitudes toward adopting ESTs was developed, and attitudes were investigated in relation to a set of individual differences (Aarons, 2004; Aarons & Sawitzky, 2006; Garland, Kruse, & Aarons, 2003; Pignotti & Thyer, 2009; Stahmer & Aarons, 2009). According to Aarons (2004) and Patterson, Dulmus, & Maguin, (2013), worker’s attitudes toward ESTs can be reliably measured and vary in relation to individual differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers’ attitudes toward new clinical practices may hamper or facilitate the adoption of ESTs into practice settings. A quick measure of workers’ attitudes toward adopting ESTs was developed, and attitudes were investigated in relation to a set of individual differences (Aarons, 2004; Aarons & Sawitzky, 2006; Garland, Kruse, & Aarons, 2003; Pignotti & Thyer, 2009; Stahmer & Aarons, 2009). According to Aarons (2004) and Patterson, Dulmus, & Maguin, (2013), worker’s attitudes toward ESTs can be reliably measured and vary in relation to individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…The studies that reported educational attainment (Aarons, 2004; Loy, 1968; Ogborne, Wild� Braun, & Newton-Taylor, 1998) found that higher-degreed workers conveyed more positive attitudes compared to those with less education. However, a more recent study found differences between the attitudes of workers with equal levels of educational attainment (Stahmer & Aarons, 2009). Aarons’s original 2004 EBPAS validation study did not find significant differences between a worker’s educational discipline and EST attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature suggests that individual worker-level factors affect decisions about whether health care agencies implement EBPs (Aarons, 2005; Patterson, Dulmus, Maguin, & Cristalli, 2013; Patterson, Maguin, Dulmus, & Nisbet, 2013). Some possible explanations for why workers are not implementing EBPs in practice are a worker’s years of experience (Aarons, 2004; Pignotti & Thyer, 2009), educational attainment (Aarons, 2004; Ogborne, Wild, Braun, & Newton-Taylor, 1998; Stahmer & Aarons, 2009), educational discipline (Aarons, 2004; Stahmer & Aarons, 2009), and students completing an intern-ship (Aarons, 2004; Garland, Kruse, & Aarons, 2003). All of these investigations suggested several factors that contribute to the successful implementation of EBPs.…”
mentioning
confidence: 99%
“…Furthermore, there is limited research on classroom-based methods (Brunner and Seung 2009). While Stahmer and Aarons (2009) found that autism early intervention providers generally reported favorable attitudes towards using evidence-based practices, little is known regarding their actual use of those strategies in practice. Finally, there is a lack of emphasis on developing symbolic play and joint attention in early childhood curricula.…”
Section: Introductionmentioning
confidence: 99%